2007
DOI: 10.4049/jimmunol.179.9.5916
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced TNFR-Related Protein Lowers the Threshold of CD28 Costimulation in CD8+ T Cells

Abstract: CD28 is well characterized as a costimulatory molecule in T cell activation. Recent evidences indicate that TNFR superfamily members, including glucocorticoid-induced TNFR-related protein (GITR), act as costimulatory molecules. In this study, the relationship between GITR and CD28 has been investigated in murine CD8+ T cells. When suboptimal doses of anti-CD3 Ab were used, the absence of GITR lowered CD28-induced activation in these cells whereas the lack of CD28 did not affect the response of CD8+ T cells to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 62 publications
8
78
1
Order By: Relevance
“…It was previously reported that GITR can initiate NF-kB signaling in primary T cells (11,25,27). To confirm this in our model, OT-I CD8 T cells were activated with peptide and subsequently stimulated with anti-GITR (DTA-1) or rat IgG.…”
Section: Gitr Enables Survival Signaling Via Enhanced Bcl-x L Expresssupporting
confidence: 66%
See 2 more Smart Citations
“…It was previously reported that GITR can initiate NF-kB signaling in primary T cells (11,25,27). To confirm this in our model, OT-I CD8 T cells were activated with peptide and subsequently stimulated with anti-GITR (DTA-1) or rat IgG.…”
Section: Gitr Enables Survival Signaling Via Enhanced Bcl-x L Expresssupporting
confidence: 66%
“…Consistent with this, we demonstrated that GITR signaling induces NF-kB, which in turn leads to induction of the prosurvival molecule Bcl-x L . Riccardi and colleagues (11) previously showed that GITR is required for CD28-mediated upregulation of Bcl-x L expression. In this study, we have observed that Bcl-x L expression is enhanced directly downstream of GITR-mediated NF-kB signaling, as early as 3 h after GITR ligation.…”
Section: /2mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the activation of GITR )/) T cells through CD28 costimulation is particularly impaired in CD8 + T cells and GITR lowers the threshold of CD28 costimulation in CD8 + T cells. 35 In the studies using systemic administration of agonistic anti-GITR mAb or GITRL immunoglobulin, the contribution of CD4 + and CD8 + T cells to the enhanced antitumour immunity was variable and this was dependent on treatment schedules, methods for injection and tumour cells used. [10][11][12][13][14] Unlike systemic administration, tumour-associated GITRL seems to enhance preferential activation of CD8 + T cells especially at the local tumour sites.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Moreover, in preclinical tumor efficacy studies, these agonistic antibodies have shown potent tumoricidal activity. [5][6][7] The current model stipulates that agonistic antibodies targeting GITR, OX40 and other costimulatory receptors on T cells directly enhance the cytotoxic effector function of T cells, while counteracting the immunosuppressive effects of immune-regulatory populations, such as regulatory T cells (Tregs).…”
mentioning
confidence: 99%